Automatic Sentiment Analyser Based on Speech Recognition (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Analysis of the Emotion of a person has been developed over the earlier period decades. The majority of the works in it spun over text emotion analysis content analyzing strategies. Yet, audio emotion analysis opinion is in the beginning phase of the research network. Our work presents the study of various algorithms of sentiment analysis to identify Emotion by dissecting the acoustic highlights of an individual's voice. The direction of study on datasets and the strategies which are utilized to recognize feeling through voice and actualized the framework to distinguish the best structure for the errand fully expecting and conveying it in a future application.